Analysis of polycyclic aromatic hydrocarbons (PAHs) and their adsorption characteristics on activated sludge during biological treatment of coking wastewater. Issue 50 (26th October 2016) - Meng, Xiaojun; Li, Haibo; Zhang, Yuxiu; Cao, Hongbin; Sheng, Yuxing
Abstract: Experiments were conducted to investigate the concentrations of PAHs and their adsorption characteristics by activated sludge in this study. Influence of sorption time, sludge concentration, and pH on PAHs adsorption was evaluated. Furthermore, the isotherms, kinetics of adsorption, and potential risk were also explored. Experimental results show that concentrations of 16 PAHs in coking wastewater sludge were 581.600–2201.633 μg/g, both Linear and Freundlich adsorption models were able to adequately describe the adsorption equilibriums of PAHs onto activated sludge. The adsorption process closely followed the pseudo-second-order kinetic model. The adsorption efficiencies of PAHs depended on the activated sludge concentration and sorption time, while that was not affected by pH. Hydrophobic interaction, distribution, and chemisorption were mainly responsible for the adsorption of PAHs, while the surface area and pore volume of activated sludge had little contribution. Results also indicate that the order of carcinogenic health risk was Benzo[a]pyrene > Dibenzo[a, h]anthracene > Benzo[b]fluoranthene > Indeno[1, 2, 3-cd]pyrene > Benzo[a]anthracene > Benzo[k]fluoranthene.